A Review on Human Pedestrian Movement System using Agent-Based Simulation and Discrete Event Simulation - Anis Izzati, Ab Fauzan; Mazlina, Abdul Majid; Allegra, Mario (American Scientific Publisher, 2018)
Human pedestrian is a complex behavior which involves various inputs and outputs and requires a lot of decision making process. By understanding fundamentals of Discrete Event Simulation (DES) and Agent-Based Simulation (ABS), it is found that both are suitable to simulate this complex movement. This paper proposed the idea of understanding how, in its basic knowledge, these two simulation models can be combined together to enhance human pedestrian movement in high density crowd areas. Its effectiveness might not be achieved without understanding factors that may affect pedestrian’s traffic flow.